PENGARUH RISOLES GLUTEN-FREE BERBAHAN TEPUNG MOCAF TERHADAP KESADARAN POLA MAKAN SEHAT MAHASISWA PADA TES PASAR DAN DEMO DAY PROGRAM WMK UNTAG SURABAYA BATCH 3 - Eva Septilia; Awin Mulyati (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
The increasing awareness of healthy eating habits among university students has created a demand for practical and nutritious food innovations. Gluten-free risoles made from mocaf (modified cassava flour) were introduced as a healthy snack alternative that is gluten-free and rich in benefits. This study aims to evaluate the acceptance and impact of consuming gluten-free risoles on students' healthy eating awareness during the market test and Demo Day of the Wirausaha Merdeka Kampus (WMK) program at Universitas 17 Agustus 1945 (Untag) Surabaya. The research methods included respondent surveys, product trials, and descriptive analysis of the collected data. Results indicated that 90% of respondents positively accepted the product, and 72% reported an increased awareness of the importance of healthy eating. The study concluded that gluten-free risoles made from mocaf are an effective culinary innovation to support the healthy lifestyles of students.